2021
DOI: 10.1155/2021/8881115
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Dornase Alfa in the Management of COVID-19-Associated Adult Respiratory Distress Syndrome

Abstract: Objective. Currently, management of acute respiratory distress syndrome (ARDS) in COVID-19 infection with invasive mechanical ventilation results in poor prognosis and high mortality rates. Interventions to reduce ventilatory requirements or preclude their needs should be evaluated in order to improve survival rates in critically ill patients. Formation of neutrophil extracellular traps (NETs) during the innate immune response could be a contributing factor to the pulmonary pathology. This study suggests the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Weber et al showed efficacy of dornase alfa in a case series of five patients with COVID-19. Toma et al came to the same conclusion in a study of 39 COVID-19 patients (Weber et al, 2020;Toma et al, 2021).…”
Section: Clinical Evidence Of Targeting Netosis In Covid-19mentioning
confidence: 54%
“…Weber et al showed efficacy of dornase alfa in a case series of five patients with COVID-19. Toma et al came to the same conclusion in a study of 39 COVID-19 patients (Weber et al, 2020;Toma et al, 2021).…”
Section: Clinical Evidence Of Targeting Netosis In Covid-19mentioning
confidence: 54%
“…Currently, clinical data regarding the inhaled DNase in COVID-19 are very limited, coming only from two small, non-randomized, case-control trials enrolled ICU patients with ARDS [17,18]. Treatment with nebulized DNase in most of the patients was associated with improved oxygenation and outcome, especially when used earlier in the disease course [17,18]. Decreased NETs remnants in bronchoalveolar lavage fluid was also described [18].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, complement activation, triggering of the NF-κB and JAK/STAT pathways, have been described as partners in COVID-19 hyperinflammation [11][12][13]. Based on these mechanisms and the current ongoing randomized control trials (RCTs), immunomodulatory treatments including anakinra, a recombinant IL-1 receptor antagonist [14], tocilizumab, an anti-IL-6 receptor antagonist [15], baricitinib, a selective JAK-1/JAK-2 inhibitor [16] and nebulized recombinant human DNase [17,18] as an agent which dismantles the generated NETs, have been administered separately in patients with COVID-19-related SRF.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, DNAse lessened ATP and ADP-induced thrombus formation in vivo, although it did not affect NET formation [169]. The DNAse inhibitor dornase alfa has recently gained attention towards COVID-19 treatment, with improvement in patient oxygenation being noted following its use in vitro and in vivo [170][171][172], while it remains to be explored whether these agents can influence clinical outcomes by halting platelet activation among other pathways. Chloramidine, a protein-arginine deiminase antagonist known for inhibiting NETosis, was also associated with reduced arterial thrombosis in vivo [173].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%